Assessment of presumed small-molecule ligands of telomeric i-DNA by biolayer interferometry (BLI). Issue 33 (5th April 2022) - Bonnet, Hugues; Morel, Maéva; Devaux, Alexandre; Boissieras, Joseph; Granzhan, Anton; Elias, Benjamin; Lavergne, Thomas; Dejeu, Jérôme; Defrancq, Eric
Abstract : Biolayer interferometry and circular dichroism spectroscopy were used to investigate the interaction between previously reported i-motif DNA ligands and folded or unfolded i-DNA in acidic (pH 5.5) and near-neutral (pH 6.5) conditions. Abstract : Biolayer interferometry (BLI) and circular dichroism (CD) spectroscopy were used to investigate the interaction between previously reported i-motif DNA (i-DNA) ligands and folded or unfolded i-DNA in acidic (pH 5.5) and near-neutral (pH 6.5) conditions. We observed that although several ligands, in particular macrocyclic bis-acridine (BisA) and pyridostatin (PDS), showed good affinities for the telomeric i-motif forming sequence, none of the ligands displayed selective interactions with the i-DNA structure nor was able to promote its formation.